Effect of Cu content on intergranular corrosion and exfoliation corrosion susceptibility of Al−Zn−Mg−(Cu) alloys - ZHANG, Meng-han; LIU, Sheng-dan; JIANG, Jing-yu; WEI, Wei-chang (Transactions of Nonferrous Metals Society of China, 2023)
The effect of Cu content on intergranular corrosion (IGC) and exfoliation corrosion (EXCO) susceptibility of Al−Zn−Mg−(Cu) alloys was investigated by electrochemical test, immersion test, electron backscattered diffraction, optical microscope, scanning electron microscope, scanning transmission electron microscope and scanning Kelvin probe force microscope. As Cu content increases from 0 to 2.6 wt.%, IGC susceptibility increases, while EXCO susceptibility first increases and then decreases, reaching the maximum at Cu content of 1 wt.%. With the increase of Cu content, the area fraction of recrystallized grains increases, and the aspect ratio of recrystallized grains first decreases and then increases; moreover, the Volta potential difference between grain boundary precipitates (GBPs) and the matrix increases, making GBPs more susceptible to corrosion. The initiation and propagation of IGC and EXCO are discussed mainly based on the features of GBPs, grain structure, and the Volta potential difference between GBPs and the matrix.